Efficacy of surgical techniques for morbid obesity and their potentials in end-stage renal disease in preparation for kidney transplantation - A. A. Zharikov; D. A. Saydulaev; S. V. Sadovnikov; I. A. Miloserdov (Вестник трансплантологии и искусственных органов)
Obesity is a modern «epidemic» not only in the general population but also among patients with end-stage renal disease (ESRD) who require kidney transplantation (KTx). The objective of this literature review is to analyze global studies on surgical methods of treating morbid obesity and their potentials in ESRD patients in preparation for KTx.